2022
DOI: 10.1186/s12885-022-10232-z
|View full text |Cite
|
Sign up to set email alerts
|

M7G-Related lncRNAs predict prognosis and regulate the immune microenvironment in lung squamous cell carcinoma

Abstract: Background N7-Methylguanosine (m7G) and long non-coding RNAs (lncRNAs) have been widely studied in cancer and have been found to be useful for assessing tumor progression. However, the role of m7G-related lncRNAs in lung squamous cell carcinoma (LUSC) remains unclear. Thus, it is crucial to identify m7G-associated lncRNAs with definitive prognostic value. This study aimed to investigate the prognostic value, correlation with tumor mutation burden, and impact on the tumor immune microenvironment… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(6 citation statements)
references
References 46 publications
0
6
0
Order By: Relevance
“…Lung cancer is one of the deadliest malignancies in the world and is the primary cause of death among cancer patients ( Siegel, Miller & Jemal, 2020 ; Mridha et al., 2022 ; Adams et al., 2023 ). Lung squamous cell carcinoma (LUSC) belongs to non-small-cell lung cancer (NSCLC), and clinical statistics show that the number of patients with LUSC accounts for about 30% of patients with NSCLC ( Li et al., 2022a ; Ding et al., 2022 ; Chen et al., 2022a ; Pan et al., 2022 ). In recent years, conventional platinum-based two-drug therapy and combination chemotherapy have remained the first-line treatments for advanced LUSC.…”
Section: Introductionmentioning
confidence: 99%
“…Lung cancer is one of the deadliest malignancies in the world and is the primary cause of death among cancer patients ( Siegel, Miller & Jemal, 2020 ; Mridha et al., 2022 ; Adams et al., 2023 ). Lung squamous cell carcinoma (LUSC) belongs to non-small-cell lung cancer (NSCLC), and clinical statistics show that the number of patients with LUSC accounts for about 30% of patients with NSCLC ( Li et al., 2022a ; Ding et al., 2022 ; Chen et al., 2022a ; Pan et al., 2022 ). In recent years, conventional platinum-based two-drug therapy and combination chemotherapy have remained the first-line treatments for advanced LUSC.…”
Section: Introductionmentioning
confidence: 99%
“…To evaluate the changes in the immune profile according to the risk score of each patient, we enumerated the abundance of different tumor-infiltrating immune cells in the tumor mass using the whole-exome expression data ( 28 ) and found that the LSCC patients with high-risk scores had a low immune inflammatory microenvironment, which was shown by significantly lower levels of tumor-infiltrating immune cells such as T- and B-lymphocytes, dendritic cells, macrophages, and neutrophils ( Figure 7A ). After that, we obtained the enrichment scores for 13 immune-associated pathways, such as the cytotoxic activity, antigen presentation, inflammation- promoting, and interferon pathways, to compare their activities between the high- and low-risk cohorts of patients.…”
Section: Resultsmentioning
confidence: 99%
“…The immune response is important in NSCLC, especially in tobacco smoke-related carcinogenesis ( 33 , 34 ). Thus, we profiled the immune cell population and activation of immune-associated pathways in the tumor microenvironment, gene set signatures in different immune cells, and immune-associated pathways from the literature ( 28 ) and utilized the molecular signature database to explore their role in LSCC ( https://www.gsea-msigdb.org/gsea/msigdb/ ). The enrichment score of each signature for each LSCC sample was then inferred based on the RNA-sequencing data and the single-sample GSEA (ssGSEA) by using the gene set variation analysis (GSVA) R package.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Appealingly, MIR22HG can affect DNA damage and breast cancer growth in recent study [ 44 , 45 ]. Intriguingly, LINC00639, CYP4F26P as well as AF131215.6 can fill the role of prognostic biomarker in many diseases [ 46 48 ].…”
Section: Discussionmentioning
confidence: 99%